Studies on the Synthesis of Novel 2,4-ThiazolidinedioneDerivatives with Antidiabetic Activity: Synthesis of 2,4-thiazolidinedione derivatives - Shashikant R. Pattan; Prajact Kekare; Ashwini Patil; Ana Nikalje; BS Kittur (Iranian Journal of Pharmaceutical Sciences, 2009)
A new series of thiazolidinedione derivatives were synthesized. The structures of these compounds were established by means of IR, 1H-NMR and elemental analysis. All of the compounds were screened for antidiabetic activity on albino rats.Most of the compounds showed significant antidiabetic activity when compared with the standard drug glibenclamide.